2009
DOI: 10.1007/s10620-009-0817-1
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Soluble CD40 Ligand and P-Selectin in Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is linked to an increased risk of cardiovascular disease. We aimed to research whether the levels of soluble P-selectin (sP-selectin) and soluble CD40 ligand (sCD40L), markers of endothelial function, are altered in subjects with NAFLD having no confounding factors for atherosclerosis. sCD40L, sP-selectin, and high-sensitivity C-reactive protein (hsCRP) levels, and homeostasis model assessment of insulin resistance (HOMA-IR) indexes were measured in 50 NAFLD subjects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…8 Prior studies have shown a similar association between hepatic steatosis and systemic inflammation. 10,14,[23][24][25][26][27][28][29][30][31]33,15,35,58,[16][17][18][19][20][21][22] In smaller studies of specific populations, radiographic hepatic steatosis is positively associated with hs-CRP, IL6, and ICAM1, consistent with our results. 30,58 Small studies also show greater hs-CRP among those with hepatic steatosis and nonalcoholic steatohepatitis (NASH).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…8 Prior studies have shown a similar association between hepatic steatosis and systemic inflammation. 10,14,[23][24][25][26][27][28][29][30][31]33,15,35,58,[16][17][18][19][20][21][22] In smaller studies of specific populations, radiographic hepatic steatosis is positively associated with hs-CRP, IL6, and ICAM1, consistent with our results. 30,58 Small studies also show greater hs-CRP among those with hepatic steatosis and nonalcoholic steatohepatitis (NASH).…”
Section: Discussionsupporting
confidence: 91%
“…In hospital-based cohorts, several studies observed an association between those with NAFLD or hepatic fibrosis and measures of systemic inflammation. 17,18,[27][28][29][19][20][21][22][23][24][25][26] Prior studies of the association between NAFLD and inflammatory makers have largely been limited by small sample sizes 16,17,[31][32][33]18,20,24,25,[27][28][29][30] or measurement of a single or few inflammatory markers 10,14,35,15,19,21,22,24,25,33,34 , and have predominantly included those with more advanced NAFLD. 23,26,29 The relationship between hepatic steatosis and systemic inflammation among community-dwellers not selected for liver disease has largely been unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Lucero et al showed that NAFLD was associated with the increase of CV biomarkers, such as high sensitivity C-reactive protein (hsCRP), TNF-α, vascular cell adhesion molecule (VCAM), intercellular adhesion molecule (ICAM) (74). The positive association between increased hs-CRP and NAFLD has been reported in both MetS (75) and healthy subjects (33,(76)(77)(78). Indeed, Lizardi-Cervera et al (76) confirmed the independent predictive value of this biomarker on CV risk (OR 5.83, 95% CI 3.07-11.06; p<0.001).…”
Section: Serum Inflammatory Biomarkers Of Nafld Might Predict Atherotmentioning
confidence: 99%
“… 34 , 35 However, the major contributor to long-term chronic allograft damage is CD4 + effector T cells, and many of the soluble mediators we found to be increased in female Hispanics with NASH can profoundly impact the function and survival of these cells, such as IL-7, IL-17A, and sCD40L. 36 43 Taken together, female Hispanics with NASH have a heightened innate immune response that quickly switches to an adaptive immune response upon transplantation, with the capacity to drive chronic inflammation-induced damage, leading to poorer outcomes.…”
Section: Discussionmentioning
confidence: 90%